Japan : Financial Sector Stability Assessment Update. (IMF Staff Country Reports; Country Report, 2012)
The macroeconomic environment of Japan has constantly been under pressure owing to rising public debt and fiscal deficits. Credit demand has been limited and has shown weak profitability. Growing risks have heightened concerns about a possible feedback to financial stability. This report summarizes the findings of the financial sector stability assessment of Japan. The Executive Board recommends a broad-based financial reform plan that could contribute to private sector growth. Suggested measures included allocating market-based credit to SMEs, improving the framework for capital markets, and consolidating and streamlining of regional banks.